OPTIMALISASI KEBIJAKAN SISTEM RUJUKAN BERJENJANG PASIEN BADAN PENYELENGGAR JAMINAN SOSIAL (BPJS) DI PUSKESMAS SAPTA TARUNA - Salim, Agus; Angela, Hairuning Suci; Aulia, Intan; Romanda, Cantika Starla Putri; Ramadhani, Indah (Awal Bros Journal of Community Development, 2025)
The tiered referral system in the National Health Insurance (JKN) program organized by BPJS Kesehatan aims to ensure effective, efficient, and medically appropriate health services for participants. However, the implementation of this system still faces various obstacles, such as inconsistent referral flow, low participant understanding of the referral mechanism, and limited facilities at the primary care level. This study aims to analyze the problems faced in the BPJS tiered referral system and provide recommendations for optimization based on information technology, improving the quality of human resources, and strengthening coordination between health facilities. The method used is a qualitative study with a descriptive approach, through interviews and analysis of policy documents. The results show that optimization of the referral system can be achieved by digitizing the referral process, continuous socialization to participants and medical personnel, and increasing the capabilities of first-level health facilities. With appropriate improvements, BPJS's tiered referral system is expected to improve access, quality, and continuity of health services for all JKN participants.